Non-reactive facet specific adsorption as a route to remediation of chlorinated organic contaminants - Guo, Hao; Gerstein, Emily A.; Jha, Kshitij C.; Arsano, Iskinder; Haider, M. Ali; Khan, Tuhin S.; Tsige, Mesfin (Frontiers in Catalysis, 2023)
The present work quantifies metal-contaminant interactions between palladium (Pd) substrates and three salient chlorinated organic contaminants, namely trichloroethylene (TCE), 1,3,5-trichlorobenzene (TCB), and 3,3',4,4'-tetrachlorobiphenyl (PCB77). Given that Pd is one of the highest catalytically active materials known for contaminant removal, maximizing catalytic efficiency through optimal adsorption dynamics reduces the cost of remediation of contaminants that are persistent water pollutants chronically affecting public health. Adsorption efficiency analyses from all-atom molecular dynamics (MD) simulations advance the understanding of reaction mechanisms available from density functional calculations to an extractable feature scale that can fit the parametric design of supported metal catalytic systems and feed into high throughput catalyst selection. Data on residence time, site-specific adsorption, binding energies, packing geometries, orientation profiles, and the effect of adsorbate size show the anomalous behavior of organic contaminant adsorption on the undercoordinated {110} surface as compared to the {111} and {100} surfaces. The intermolecular interaction within contaminants from MD simulation exhibits refreshing results than ordinary single molecule DFT calculation. Since complete adsorption and dechlorination is an essential step for chlorinated organic contaminant remediation pathways, the presented profiles provide essential information for designing efficient remediation systems through facet-controlled palladium nanoparticles.